2017
DOI: 10.1002/jhbp.410
|View full text |Cite
|
Sign up to set email alerts
|

Systematic extrahepatic Glissonean pedicle isolation for anatomical liver resection based on Laennec's capsule: proposal of a novel comprehensive surgical anatomy of the liver

Abstract: Anatomical liver resection with the Glissonean pedicle isolation is widely approved as an essential procedure for safety and curability. Especially, the extrahepatic Glissonean pedicle isolation without parenchymal destruction should be an ideal procedure. However, the surgical technique has not been standardized due to a lack of anatomical understanding. Herein, we proposed a novel comprehensive surgical anatomy of the liver based on Laennec's capsule that would give a theoretical background to the extrahepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
163
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(181 citation statements)
references
References 6 publications
5
163
0
4
Order By: Relevance
“…Furthermore, Sugioka recently reported that Glisson's capsule and Laennec's capsule can be divided outside and inside the liver. Therefore, the Glissonean pedicles can be separated from Laennec's capsule and not only the main portal pedicles but also the sectional and segmental pedicles can be approached at the hepatic hilus without liver dissection . This concept supports Takasaki's procedure.…”
Section: The Extrafascial Approachmentioning
confidence: 76%
“…Furthermore, Sugioka recently reported that Glisson's capsule and Laennec's capsule can be divided outside and inside the liver. Therefore, the Glissonean pedicles can be separated from Laennec's capsule and not only the main portal pedicles but also the sectional and segmental pedicles can be approached at the hepatic hilus without liver dissection . This concept supports Takasaki's procedure.…”
Section: The Extrafascial Approachmentioning
confidence: 76%
“…There is a relatively dense connective tissue on the liver side and sparse connective tissue on the diaphragm side of the fused peritoneal peritoneum. The structure composed of dense connective tissue on the liver side and liver serosa is the Laennec's capsule [12,13]. Because the liver surface of the bare area is covered with the Laennec's capsule, as shown in our study, the phrase "bare area" may not be appropriate.…”
Section: Discussionmentioning
confidence: 82%
“…In our method, however, the RHV trunk can be isolated with a thick wall by attaching the fibrous tissue around it. This tissue ("Laennec's capsule") essentially covers the liver parenchyma (5) Brief report | 5 can be intentionally preserved on the RHV wall by exposing it from the root side (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%